Relationship between social support and schizophrenia relapse among patients with schizophrenia on follow-up at Amanuel Mental Specialized Hospital, Addis Ababa, Ethiopia: A case-control study - Samuel, Tinbete; Nigussie, Kabtamu; Mirkena, Yohannes; Azale, Telake (Frontiers in Psychiatry, 2022)
Abstract Background: Severe mental illnesses affect about 4% the adult population worldwide. The illness is highly related with relapse rate and can cause cognitive, social and functional deterioration on the patients. While, there are some factors known to be protective of relapse occurrence in schizophrenia, having a good social support is found to be one of the strongest factor. Therefore, aim of this study to identify the association between relapse and poor social support in patients with schizophrenia. Methods: Unmatched case-control study was carried out among 408 schizophrenia patients on a follow up at Amanuel mental specialized hospital from March to May, 2020. Convenience sampling technique was used to draw the participants. Social support was assessed by Oslo social support scale. Epidemiological Information version 7 was used for data cleaning coding and entry after that the data was exported to statistical package for social science version 22 for analysis. Chi-square test, unconditioned binary logistic regression analysis and bivariate correlation analysis was carried. Results: Majority of the participants were male with 137 cases and 140 controls. The mean and standard deviation age of participants was 36.06 ±9.842 years. From 194 cases 61.1% of them reported as having poor social support. In multiple logistic regression only social support was found statistically significant (p<0.001, AOR=3.102, CI (95%) = (1.985-4.848). Hence, the odds of having relapse were 3.102 higher in those who have a poor social support when compared to those with good social support. Emotional involvement, financial problems and stressful life events were found to indirectly affect relapse by having negative correlation with social support. Conclusion: The study showed there was a relationship between relapse and social support and this indicates that social support can be a good predictor of schizophrenia relapse. The care givers and clinicians of the patients should increase their support to the patients, hospitals with mental health services to better encourage formation of social support for the patients; including psychosocial interventions which will be to enhance the social support system.